Predictors of infectious pathology in the neonatal period - O. A. Shulakova; K. G. Gurevitch; S. K. Zyryanov (Кубанский научный медицинский вестник)
In last years has been growth in the number perinatal morbidity, including to infectious diseases in the neonatal period. The article presents the main risk factors for antenatal, intrapartum and neonatal period. The work was conducted he work was based on a retrospective analysis of medical documentation in a group of children hospitalized hospital from home. These children were discharged from another hospital in a satisfactory condition. The article presents the most important risk factors, which must pay attention to the doctor neonatologist and obstetrician. The main are: somatic, obstetrics and infectious anamnesis of women before and during pregnancy, parity of women, the use of reproductive technologies, childbirth methods and course after birth period, infant feeding, epidemiological anamnesis.